Self-Efficacy, Teaching Practice, and Teacher Readiness: Mediating Role Teacher Interest - Hervina Renovaka Pradev Devi; Riza Yonisa Kurniawan; Mohamad Zuber Bin Abd Majid (International Journal of Emerging Research and Review, 2023)
Objective: In the realm of education, the effectiveness of teaching practices and the readiness of teachers to navigate the challenges of the classroom environment have garnered substantial attention. One pivotal aspect that has emerged in educational research is the concept of self-efficacy – the belief in one's capabilities to accomplish tasks and produce desired outcomes. Self-efficacy is known to significantly influence various aspects of an individual's professional life, including teaching. The correlation between self-efficacy, teaching practice, and teacher readiness has been a subject of interest for educators and researchers alike. This research aims to determine the effect of self-efficacy and teaching practice on readiness to be a teacher through interest in becoming a teacher as a mediation variable. We used an online questionnaire to identify 435 college students for this study. Method: We applied partial least squares structural equation modelling (PLS-SEM) to analyze the research model. Results: The results showed that the exogenous variables, namely self-efficacy and teaching practice, significantly affected the readiness to become teachers directly. Novelty: Whereas indirectly, self-efficacy does not affect readiness to become a teacher through an interest in becoming a teacher. However, it differs from the teaching practice variable, which indirectly affects readiness to become a teacher through an interest in becoming a teacher.